The Fight for an AIDS-Free World: Confronting the Stigma, Reaching the Marginalized - Dorothy Serwaa Boakye; Emmanuel Kumah; Samuel Adjorlolo (Ubiquity Press, 2024)
Background: Despite biomedical advances, HIV/AIDS continues to concentrate among marginalized populations facing stigma, discrimination, and barriers to equitable prevention and care. This paper explores the global, national, and regional initiatives implemented to confront stigma to enhance the engagement of key populations in ending AIDS. Methods: A non-systematic search was conducted, focusing on current statistics on disproportionate HIV burden and mortality among groups such as gay and bisexual men, people who inject drugs, transgender people, sex workers, and prisoners; barriers faced; programs overcoming stigma to expand access; policy and social strategies prioritizing stigma elimination; and vision for collaborative action across sectors to address inequities enabling persistent transmission. Relevant data was extracted from the selected publications and summarized qualitatively based on the main themes of the study. Results: Stigma emerges as an amplifier of transmission risks and obstacles across the care continuum among key populations, with criminalization and social marginalization exacerbating barriers. Initiatives successfully countering stigma are highlighted, like peer navigation services, mobile clinics, telehealth expansion, and advocacy campaigns. Structural reforms are urged around healthcare system changes, legal protections, and community empowerment efforts centered on affected populations' leadership. Conclusion: Ending AIDS as an epidemic requires advancing scientific interventions through social interventions deliberately confronting stigma to ensure equitable engagement and access for key groups that ongoing marginalization places at risk. Realizing improved outcomes depends on collective action across sectors prioritizing human rights, inclusion, participatory policymaking, and access expansion targeting those still left behind.